Pengembangan model kedekatan pertemanan berdasarkan resiprositas, kesetaraan dan dukungan - Aulia, Wina (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2025)
Individuals need close friends. How is close friendship developed? Generally, closeness in friendship can be developed and maintained if the relationship is equal and mutually supportive. The purpose of this research is to develop a model of friendship closeness, with reciprocity as the antecedent and equality and support as mediators. The participants in this research were 234 first-year students at Universitas Gadjah Mada. Data were collected by survey method. Closeness, reciprocity, equality and support were measured by Likert-like scales which met the criteria for psychometric property tests. Structural Equation Modeling (SEM) with four latent variables was applied to test the model’s fit with the data. The model of closeness in friendship which was developed by reciprocity and mediated by equality as well as support showed a good fit with the empirical data, as confirmed by strong parameter estimates. Some practical implications of this research are proposed.